Immediate Complete Overdenture – A case report - Fatahillah, Ali Surahman; Kridanto Kamadjaja, Michael Josef; Laksono, Harry (Indonesian Journal of Dental Medicine, 2018)
Background: Edentulousness resulting from extraction of teeth often leads to psychological problem and social isolation of the patient. The patient has to adapt to the situation with respect to speech, chewing, swallowing, and so forth. A smooth transition from dentulousness to edentulousness is the result of immediate over denture with a few retained teeth. Purpose: to report overdenture prevents alveolar ridge bone absorption, stabilizes a denture, and makes the typical sensory function to be looked closer to natural teeth. Case: A 79-year-old female complaint of missing multiple teeth and desire to replace them. Extraoral examination and temporomandibular joint movement were normal. Five teeth (12,11,21,22,34) exhibited grade II mobility with diagnosis apical chronic periodontitis. Radiographic examination is an overview of diffuse radiolucent on the apical on the teeth 17,13,12,11,21,22,34. Case Management: First, make a diagnostic impressions of the maxillary and mandibular with irreversible hydrocolloid then poured in dental stone. After that, the final impressions were taken and poured in dental stone, casts mounted on articulators. Bite registration was done after using bite rim and bite registration material. The next step is setting up the artificial teeth then tried to the patient. Five teeth (12,11,21,22,34) were trimmed from the casts on the functional model. The patients tooth 12, 11, 21,22 and 34 were reduced to a dome shape only 2 mm above gingival margin then restored with GIC on the surface. The denture was then placed immediately after reduced. Discussion: The selected abutments teeth were reduced to a dome shape only 2 mm above gingival margin. This will create adequate space for the overlying artificial denture tooth and denture base. Also, it reduces the lateral stresses and lever action of the tooth. The retained tooth roots, used for overdenture, transfers occlusal forces to the alveolar bone through the periodontal ligament and maintain alveolar ridge morphology. Conclusion: Overdenture can be used to prevents alveolar ridge bone absorption, stabilizes a denture, and makes the typical sensory function to be looked closer to natural teeth.